2005
DOI: 10.1007/s00122-005-0164-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sterility-inducing cytoplasms in rye using the plasmotype–genotype interaction test and newly developed SCAR markers

Abstract: A series of 25 rye (Secale cereale L.) inbred lines was tested with respect to three mitochondrial sequence-characterized amplified region (SCAR) polymorphisms. The analysis revealed a close association between the marker-determined mitotypes and plasmotypes (cytoplasm types known from breeding data) represented by the inbreds. The mitochondrial markers also confirmed normal (N-) cytoplasmic character of three wild rye species: Secale montanum, S. vavilovii and S. kuprijanovii. For 186 plants from open-pollina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The discovery of effective restorer genes for CMS-P in rye originating from South America (Geiger and Miedaner 1996;Miedaner et al 1997) is in agreement with the CMS-P cytoplasm occurring in different populations from this region, as reported previously (£apiñski and Stoja³owski 2003;Stoja³owski et al 2006) and confirmed in this study.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The discovery of effective restorer genes for CMS-P in rye originating from South America (Geiger and Miedaner 1996;Miedaner et al 1997) is in agreement with the CMS-P cytoplasm occurring in different populations from this region, as reported previously (£apiñski and Stoja³owski 2003;Stoja³owski et al 2006) and confirmed in this study.…”
supporting
confidence: 92%
“…by Kobylyanskii (1971Kobylyanskii ( ), £apiñski (1972, Madej (1975), and Adolf and Winkel (1985). It is known that the CMS-V cytoplasm frequently occurs in European rye breeding materials, while the CMS-P type was identified mainly in South American populations (£apiñski and Stoja³owski 2003;Stoja³owski et al 2006). Knowledge of the cytoplasmic structure of rye cultivars is important, since the presence of sterilizing cytoplasm forces a natural selection eliminating non-restorer alleles from populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Митохондриальные маркеры также подтвердили наличие индуцирующей сте-рильность цитоплазмы в остальных 109 растениях. Кроме того, с помощью маркеров можно было различить расте-ния, имеющие Р-или V-тип цитоплазмы, а также удалось выявить широкую распространенность индуцирующей стерильность цитоплазмы, особенно в южноамериканских популяциях (Stojałowski et al, 2006).…”
Section: филогенетические и популяционно-генетические исследования роunclassified